1999
DOI: 10.1159/000013822
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Strain-Related Differences in Dehydrogenase Activity and Glycogen Levels in CBA and C57 Mouse Cochleas

Abstract: In the C57 mouse strain, loss of sensory hair cells (HCs) begins during early adulthood, starting in the base of the cochlea and progressing toward the apex as aging continues. In contrast, the CBA mouse strain exhibits no significant cochlear histopathology until relatively late in life. These strain and age differences may be related to differences in cochlear energy metabolism. To examine this possibility, we used dehydrogenase and glycogen histochemistry to evaluate the metabolic capacities of HCs and stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The bullae were quickly removed and opened to expose the cochleae. The round window, oval window, and apex of the cochleae were opened and the cochleae perfused with a succinate dehydrogenase staining solution (2.5 ml of 0.2 M sodium succinate, 2.5 ml of 0.2 M phosphate buffer, pH 7.6 and 5 ml of a 0.1% nitroblue tetrazolium solution) [Ding et al, 1999]. The cochleae were immersed in the staining solution at 37°C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…The bullae were quickly removed and opened to expose the cochleae. The round window, oval window, and apex of the cochleae were opened and the cochleae perfused with a succinate dehydrogenase staining solution (2.5 ml of 0.2 M sodium succinate, 2.5 ml of 0.2 M phosphate buffer, pH 7.6 and 5 ml of a 0.1% nitroblue tetrazolium solution) [Ding et al, 1999]. The cochleae were immersed in the staining solution at 37°C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…The treated rats had better cochlear function than control rats that were fed a placebo. In another study on rodents, Ding et al [1999] found evidence that age-related changes in the inner ear of CBA mice were correlated with altered energy metabolism. Whereas a good deal more research needs to be done, the data indicate that some forms of presbycusis are associated with mitochondrial dysfunction in cochlear cells and suggest new therapeutic directions aimed at mitochondrial health [see also Fischel-Ghodsian, 1999;Seidman et al, 1996a.…”
Section: Mitochondrial Damagementioning
confidence: 98%
“…72,73 After the final ABR test, the mice were deeply anaesthetized with an overdose of ketamine, and the cochleae rapidly harvested. Surrounding soft tissues were removed and the round window and oval window were both opened.…”
Section: Cytocochleogrammentioning
confidence: 99%